(untitled) (ModaPalavra e-periódico, 2023)
The above article aims to research the social dimension of sustainability, focusing on the principle of valuing and including local communities in fashion projects, through Ronaldo Fraga’s collections. The methodology for obtaining the data started with a bibliographical research to define the objectives and build the state of the art, later, a case study was carried out from two Ronaldo Fraga collections, to investigate how the designer values ​​and includes communities finally, for the qualitative analysis of the data, the technique of content analysis was based on her fashion projects. It is concluded that the collections chosen for analysis in this symbolic work as the stylist manage to put relevant questions for society in their creations, referring to debates about the mode of production of the fashion industry, as well as conscious consumption and integration with resources from the own country, these being ideological aspects of sustainability.